THỬ NGHIỆM ANOT MAGNETITE TRONG HỆ THỐNG BẢO VỆ ĐIỆN HÓA CHỐNG ĂN MÒN VỎ THÉP TÀU BIỂN - Nguyễn, Trọng Hiệp; Nguyễn, Hồng Dư; Lưu, Phương Minh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
TESTING OF MAGNETITEANODE USED IN THE ELECTROCHEMICAL SYSTEM TO PREVENT CORROSION OF STEEL HULL IN SEAWATER The paper presents the testing results of magnetite anode used in the impressed current cathodic protection system to prevent corrosion of steel hull in the seawater at Nha Trang bay. Testing results for steel hull with an submerged area of 300 m2 in seawater showed that anodic current reached 0.7 ÷ 1.5 A, the largest anodic current density reached 764 A/m2, the voltage shift of hull is from -156 mV to -259 mV. The voltage of the hull compared to Ag/AgCl reference electrode meets cathodic protection standards in the seawater.